The politics of prison crowding: a critical analysis of the Italian prison system - Santorso, Simone (Routledge frontiers of criminal justice, 2023)
"The Politics of Prison Crowding investigates recent transformations in Italy's penal system to make the key analytical observation that conditions of overcrowding have become the 'new normal' under which the modern prison system continues to operate and deliver punishment. Engaging with the politics of crowding thus entails a direct and pertinent engagement with the modern state's politics of criminal justice and social control. Worldwide over the last decades, a growing number of jurisdictions have prison systems operating above or to the limit of their capacity, yet little attention has been paid to these elements in the analysis of prison politics and day-to-day function. By exploring the crowding issue, this book offers an original and interesting insight into the politics and dynamics characterising contemporary prison systems. The hypothesis of this study is that the politics of prison crowding have become the template for the daily administration of the prison system, which incorporates not just policy and rules but day-to-day functions and practices regulating life behind bars. Through interviews in modern Italian prisons, the book brings to light a radical redefinition of a carceral system that harshens the delivery of punishment while justifying this exacerbation of pain by adding new bureaucratic logic to the administration of the penal system within a narrative of compliance to human rights standards. By shedding new light on prison politics to open new critical perspectives and research paths, The Politics of Prison Crowding offers a fundamental tool to scholars, students and all professional policymakers and practitioners dealing with prison policies and the politics of justice"--